1985
DOI: 10.1007/bf00402503
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes of Hodgkin's disease contain an antigen that is present in Hodgkin and reed-sternberg cells

Abstract: Circulating immune complexes (CIC), isolated from the serum of a patient with Hodgkin's disease (HD) and from control serum (CS) of healthy adults, were used to generate heterologous antisera in rabbits. The antiserum directed against CIC from HD (AS-HD) and the antiserum directed against CIC from CS (AS-CS) were used to identify immunoglobulins, complement factors and alpha2-macroglobulin as immune complex components. After adsorbing both antisera with normal human sera, we found that the adsorbed AS-HD was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Aberrations of the humoral immunity include the presence of immune complexes in sera of patients with Hodgkin's disease. Previous investigations revealed that these immune complexes contain antigens that are present in the cytoplasm of H&RS cells (37). However, the nature of these antigens has remained undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrations of the humoral immunity include the presence of immune complexes in sera of patients with Hodgkin's disease. Previous investigations revealed that these immune complexes contain antigens that are present in the cytoplasm of H&RS cells (37). However, the nature of these antigens has remained undefined.…”
Section: Discussionmentioning
confidence: 99%
“…1975). Elevated levels of immune complexes are also associated with several types of human cancers, including melanoma (Jerry et al, 1976), GI malignancy (Ristow et a/., 1979), Hodgkin's disease (Bepler et al, 1985), and breast (Krieger et al, 1983) and lung cancer (Garcia et al, 1987;Bukh eral., 1988;Lowe et al, 1981). Circulating immune complexes have been found, by a variety of techniques, in the sera of patients with cancer, and levels have tended generally to correlate with stage of disease in most series (Ruiz-Arguelles et a/., 1982;Theofilopoulos et al, 1977).…”
mentioning
confidence: 99%